2019
DOI: 10.1093/omcr/omz003
|View full text |Cite
|
Sign up to set email alerts
|

Kindler syndrome: a rare case report from Greece

Abstract: Kindler syndrome is a rare autosomal recessive inherited disease characterized by infantile acral bullae, progressive poikiloderma, cutaneous atrophy, photosensitivity and various forms of mucosal involvement. In this paper, we report a case of a 49-year-old Greek Caucasian male aiming to emphasize the importance of genetic analysis as a gold standard of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Only 23 mutations were revealed to be recurrent in >1 report. Notably, c.676insC was the most common mutation reported in 11 different reports (7,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in multiple populations, including German, Albanian, Kosovian, Turkish, Serbian-Greek, Pakistani, Serbian, Australian, Indian, Brazilian and Greek Caucasian, indicating that c.676insC may be a mutation hotspot and serve as a founder effector in the genetic pathogenesis of KS. Furthermore, c.910G>T occurred in 6 reports (20,23,25,27,32,33), c.328C>T in 5 reports (9,20,23,34,35), c.1718+2T>C in 4 reports (20,22,36,37) in multiple different populations and appeared to be relatively common in FERMT1.…”
Section: Discussionmentioning
confidence: 98%
“…Only 23 mutations were revealed to be recurrent in >1 report. Notably, c.676insC was the most common mutation reported in 11 different reports (7,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in multiple populations, including German, Albanian, Kosovian, Turkish, Serbian-Greek, Pakistani, Serbian, Australian, Indian, Brazilian and Greek Caucasian, indicating that c.676insC may be a mutation hotspot and serve as a founder effector in the genetic pathogenesis of KS. Furthermore, c.910G>T occurred in 6 reports (20,23,25,27,32,33), c.328C>T in 5 reports (9,20,23,34,35), c.1718+2T>C in 4 reports (20,22,36,37) in multiple different populations and appeared to be relatively common in FERMT1.…”
Section: Discussionmentioning
confidence: 98%
“…Microstomia, or restricted mouth opening, probably due to fibrosis of the commissures, has been reported in several patients with KEB (Image 2.19). 4,132,135,138,155,156,[165][166][167][168][169][170][171][172] However, many patients do not complain of this functional problem. No studies have been identified on the severity or prevalence of this feature.…”
Section: Microstomiamentioning
confidence: 99%
“…While some patients, particularly younger cases, do not report involvement of the oral mucosa, [173][174][175][176] others report few ulcers 164,177,178 and a third group presents fragile mucosa and painful ulcers scattered throughout the oral mucosa, affecting the alveolar ridge, soft palate, lip, and floor of the mouth. 133,162,164,165,179,180…”
Section: Intraoral Soft Tissue Involvementmentioning
confidence: 99%
See 2 more Smart Citations